2016
DOI: 10.3390/su9010017
|View full text |Cite
|
Sign up to set email alerts
|

Be Sustainable to Be Innovative: An Analysis of Their Mutual Reinforcement

Abstract: Sustainable development has attracted the increasing attention of both researchers and practitioners. While academicians and practitioners' focus towards sustainability has shifted to innovation, there is a need to understand how sustainability and innovation are interlinked. Thus, this paper attempts to analyze, first, the bidirectional impact of the firms' pursuit of sustainability and innovation as the priority, second, the bidirectional impact of the adoption of sustainability innovation action programs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 100 publications
1
30
0
1
Order By: Relevance
“…Besides, several studies have established the positive influence of CSR and the environment on consumer behavior (Boccia & Sarnacchiaro, ; Laroche et al, ; Lerro et al, ; Ramesh et al, ).Therefore, firms are encouraged to engage in CSR activities to appeal to consumers' EAPTs and EISTs in a vigorous, energetic, and comprehensive manner. Moreover, sustainability is an essential part of an organization's survival in the modern and fiercely competitive environment (R. J. Baumgartner & Ebner, ; Behnam & Cagliano, ). To build and maintain relationships with consumers, firms have to engage them by adopting CSR practices and being socially responsible.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, several studies have established the positive influence of CSR and the environment on consumer behavior (Boccia & Sarnacchiaro, ; Laroche et al, ; Lerro et al, ; Ramesh et al, ).Therefore, firms are encouraged to engage in CSR activities to appeal to consumers' EAPTs and EISTs in a vigorous, energetic, and comprehensive manner. Moreover, sustainability is an essential part of an organization's survival in the modern and fiercely competitive environment (R. J. Baumgartner & Ebner, ; Behnam & Cagliano, ). To build and maintain relationships with consumers, firms have to engage them by adopting CSR practices and being socially responsible.…”
Section: Discussionmentioning
confidence: 99%
“…In reality, Fliaster and Kolloch [154] researched green innovation and found that it is likely to be affected by the interactions between primary and secondary stakeholders and, it is further expected to ensure profitability. In addition, there is evidence that innovation in the products and processes of companies generates social, organizational, and financial results [77,155,156]. Due to this, we can posit the eighth hypothesis: H8.…”
Section: Innovation and Profitabilitymentioning
confidence: 99%
“…The concept, even today, is not entirely understood by companies, where there is some confusion about its conceptualization, especially in its environmental dimension [1]. However, there are ample studies that reflect a positive relationship between the adoption of eco-innovation and sustainability [2][3][4], considering eco-innovation as a priority antecedent of sustainability.…”
Section: Introductionmentioning
confidence: 99%